Implementasi Program Bantuan Dana Desa di Tengah Pandemi Covid 19 - Risna Dewi; Tommy Adista; Safrida Safrida (Jurnal Public Policy, 2021)
The Corona virus is a new virus that emerged at the end of December 2019, it is called Covid-19. The virus attacks the respiratory system which is very dangerous and deadly. The problem in the village of Utenkot, Muara Dua Subdistrict, in its implementation, the Uteun Kot Village Government has allocated a special fund of Rp. 597,650,000. This type of research is descriptive qualitative research using techniques to obtain data through interviews, observation and documentation. The research objective is to describe the implementation of the village fund program in the midst of the Covid-19 period through village funds in Gampong Uteun Kot along with the efforts made by geuchik in dealing with COVID-19. Data analysis techniques are achieved through data collection, data reduction, data presentation and data levers. Informants were determined intentionally, consisting of the Head of Muara Dua Sub-District, Gampong Geuchik, Tuha Pheut, Hamlet Head, Community Leaders, Youth Leaders and Community Members with ODP status. The results showed that Uteun Kot Gampong Geuchik had allocated Rp. 597,650,000 to provide direct cash assistance of Rp. 600,000 / household. Other efforts include orders for a covid-19 task force, public education, a covid-19 information system and provision of means of washing people's hands. In conclusion, the efforts made by Geuchik to tackle the corona-19 virus outbreak in Uteun Kot Village were providing direct cash assistance of Rp. 600,000 per household, of which only 120 households / HH received the assistance, the formation of a covid-19 task force, with comply with Health protocol.